UNDIAGNOSED CELIAC DISEASE IN PATIENTS PRESENTING WITH IRRITABLE BOWEL SYNDROME SYMPTOMS - Khayyat, Yasir Mohammed (Journal of Ayub Medical College Abbottabad, 2020)
Background: Irritable bowel syndrome (IBS) is a common clinical condition that is often diagnosed based on a set of clinical criteria. Celiac disease (CD) has a similar symptom. The study aims to estimate the prevalence of undiagnosed celiac disease (CD) in patients with criteria-positive IBS and compare with healthy control. Methods: A Case control study conducted from August 2013 to July 2016. For the control group with negative ROME 3 criteria for IBS provided serum total immunoglobulin (IgA) level and serum tissue transglutaminase antibody (tTG IgA). The case group with positive criteria interviewed, examined, competed ROME 3 questionnaire and provided blood sample for haematology, biochemistry, and serum tTG IgA and IgG. Positive for CD invited for upper endoscopy and duodenal biopsy for evaluation of pathological involvement using the modified Marsh classification. Results: Three controls (1.47%) and 21 cases (6.9%) had positive serology for CD. A statistically significant association found between serum tTG positivity and IBS and IBS-diarrhoea subtypes. No correlation was found between tTG positivity and age and sex of the case group. Conclusions: Celiac disease is common in IBS patients especially those with criteria-positive diagnosis. Serology screening for CD is helpful in IBS and IBS-D patients. Keywords: Diarrhoea; Irritable Bowel Syndrome; Celiac Disease; Disorder; Functional gastrointestinal